PENGEMBANGAN TRAINER SELF BALANCING ROBOT BERBASIS ESP 32 SEBAGAI MEDIA PEMBELAJARAN PADA MATA PELAJARAN PENGENDALI SISTEM ROBOTIK DI SMKN 1 TAMBELANGAN - Satria, Farid Satria; Zuhrie, M. Syariffuddien; Baskoro, Farid; Fransisca, Yulia (Universitas Negeri Surabaya, 2021)
The development of technology makes education in Indonesia have to adjust the material to be studied by students. The results of observations that have been carried out at SMK Negeri 1 Tambelangan in the Industrial Electronics Engineering expertise program are that there is no learning media for self balancing robots based on ESP 32. The aim of the research is to create learning media for trainers and textbooks for self balancing robots based on ESP32 which are suitable for use include: and textbooks, the practicality of trainers and textbooks in terms of student responses, the level of effectiveness of trainers and textbooks in terms of student learning outcomes. Research and Development (R&D) with a One Shot-Case Study trial design and research subjects, namely 25 students of class XII Industrial Electronics Engineering SMK Negeri 1 Tambelangan, were used as the method of this research. On the validity aspect of the learning media in the form of a trainer it is declared very valid with a value of 91.1%, textbooks are declared valid with a value of 79.5% and instruments are declared valid with a value of 81.3%. In the aspect of trainer practicality, in terms of student responses, it can be stated that it is very practical with a score of 86.6%. In the aspect of effectiveness, the mean value is 78.79 with a value of Sig2.(2-tailed) of 0.000, the t-test after the t test analysis is 7.135 while the ttable is 2.064, then the value of tcount> ttable, meaning reject H0. Thus, the use of the ESP 32-Based Self Balancing Robot Trainer in the Robotic Control System subject for class XII Industrial Electronics Engineering at SMK Negeri 1 Tambelangan can be declared to have a good and proper effect as a learning medium in learning activities.